Scaling Design of the Pressure Response Experimental Facility for Pressure Suppression Containment - Liu, Xinxing; Meng, Zhaoming; Zhang, Nan; Sun, Zhongning (Frontiers in Energy Research, 2020)
Pressure suppression containment has been adopted extensively in the BWR reactor design due to the remarkable pressure suppression capacity. In order to study the pressure response characteristics of the containment in the initial stage of the loss of coolant accident, it is necessary to build the scaling facility to simulate the prototype. The analysis of the blow down source term and the steam condensation occurred in the suppression pool are conducted respectively for the prototype PWR. The suppression pipe system resistance term is also scaled with a certain ratio. The length and the diameter of the mian pipe and the branch pipe as well as the orifice diameter are calculated. At last, the prototype and the experiment facility are modeled by MELCOR to scale the source term. The results show that the scaling method in this paper is effective to predict the pressure evolution in the prototype containment during the loss of coolant accident.